Clothes that Click Leaders Guide - Joy Cantrell Jordan; R. Nadine Hackler (EDIS)
Produced by the Department of Family, Youth and Community Sciences in cooperation with the Florida 4-H Youth Program, University of Florida Cooperative Extension, Institute of Food and Agricultural Sciences, January, 1998; Reviewed June 2002.